Preferred Source and Perceived Need of More Information about Dental Implants by the Undergraduate Dental Students of Nepal: All Nepal Survey - Arati Sharma; Bidhan Shrestha; Bijay Kumar Chaudhari; Pramita Suwal; Raj Kumar Singh; Surya Raj Niraula; Prakash Kumar Parajuli (International Journal of Dentistry)
Objectives. This study was conducted to know the preferred source and perceived need of more information about dental implants by the undergraduate students of Nepal and their association with academic levels and gender. Materials and Methods. It was conducted in all the dental colleges of Nepal from June 2016 to June 2017 after taking ethical clearance and approval from the research committee of BPKIHS. It included all those who were present at the time of survey. Data collection was done through a cross-sectional questionnaire survey during the academic schedule of the colleges, supervised and monitored by the investigators themselves. The collected data were coded and entered in Microsoft excel 2013, and statistical analysis was done by SPSS 20 version. Result. A majority of the respondents agreed that they were not provided with sufficient information about implant treatment procedures during their BDS program (65.3%), would like more to be provided in the curriculum (95.1%), and would like to get additional reliable information from dental consultants and specialists (40.7%) and training on it from fellowship programs conducted by universities (39.2%). Significant association was seen between the responses and academic levels. Conclusion. Undergraduate dental students of Nepal want more information about dental implants through various means.